Partilha de recursos entre espécies da ictiofauna de poças de marés da Zona Costeira Amazônica - SANTOS, Annanda Carla Coelho dos (2018)
Studies about trophic ecology and sharing resources are important to understand ecological relations among species in an assembly. Thus, aim to analyses the diet of eight species from ichthyofauna of tidal pools from Amazon Coastal Zone finding to verify which were the feed strategies used for this species, the composition and specialization of diet in both periods (rainy and dry), furthermore, to understand the feeding strategies utilized by species to allow resource sharing. The samplies occurred in 80 tidal pools spread in 5 beaches of Amazonian coast (Algodoal, Areuá, Fortalezinha, Maçarico e Marieta). Diet analysis was made through food importance index (IAi%), specialization of diet was obtained by Amundsen diagram using frequency of occurrence (FO%) and specific weight (PME%). The Niche overlap was estimate through Morisita's overlap index, the validation of results was made by Ecosin v.7.42 software. The food item Petrolisthes armatus was the most significant, the remaining itens was Brachyura, crustacean exoskeleton, Gastropoda and Polichaeta. All species had low value of niche breadth in both periods with approximate values. Was observed high values of niche overlap among some species in all periods. Nevertheless, the different feed strategies and distribution patterns further high abundance of main resource consumed may have been the factor of to minimize possible competitions.